Incorporação de micronutrientes em formulado NPK e o efeito na nutrição e produtividade da soja - Sarkis, Leonardo Fernandes (2020)
The objective of this work was to reevaluate patterns of nutritional needs in B, Zn, Mn and Cu along the soybean and corn cycle from different forms of adding these micronutrientes to NPK. The treatments used were: NPK 02-20-20 without micronutrients (T1); NPK 02-20-20 + granulated micronutrients (T2); NPK 02-20-20 + micronutrients in concentrated suspension (T3) and NPK 02-20-20 + micronutrients in powder (T4), in addition to the control that received no fertilizer (C). The field experiment was conducted at the Palheta farm, located in the municipality of Luminárias -MG, in a red Argisol, cultivating soybean and corn in succession in the 2018/2019 harvest. This experiment was carried in bands, adopting a completely randomized design (DIC), with 8 lines spaced by 0.6m and 24m in length per treatment. The greenhouse experiment was conducted at the Department of Soil Science, UFLA. Samples of sandy and clayey soil with low fertility previously prepared were used to achieve increasing bases saturations. The adopted design was in randomized blocks in a factorial scheme (4x5), with 4 treatments + control and 4 saturation by bases (40, 50, 60 and 70%). All results were submitted to the normality test and subsequently to the analysis of variance and the treatments were compared by the t-student test (LSD) at the level of 5% significance. All statistical analyzes were performed using the SISVAR 5.3® software. The decreasing order of the maximum extraction of these micronutrients by soy throughout the cycle was Mn> Zn> B> Cu. However, the decreasing order of micronutrient exports by soybeans throughout the cycle was Zn> Mn> Cu> B. The quantities of Zn, Cu, Mn and B exported by soybeans corresponded to 43; 23; 20 and 9.4%, respectively, in relation to the total extracted by the culture throughout the cycle. Keywords